Moles [there's something stirring underground ...] - Strong, Andrew (Scholastic, 2009)
"Alf loves working at his family's hotel and would do anything to stop it closing, but it's such a dump, even the rats are leaving. Along with some of the hotel's crazy staff and guests, Alf's determined to save it, but how? Finding buried treasure, or solving the puzzling mystery of the Invisible Claw?"--Back cover
Keywords: Hotelkeepers / Juvenile fiction